Physical property and gas transport studies of ultrathin polysulfone membrane from 298.15 to 328.15 K and 2 to 50 bar: atomistic molecular simulation and empirical modelling - Yiin, Chung Loong; Lau, K. K.; Lock, S. S. M.; Norwahyu, Jusoh; Shariff, A. M.; Yeong, Y. F.; Syed Ali, Ammar Taqvic (Royal Society of Chemistry, 2020)
Elucidation of ultrathin polymeric membrane at the laboratory scale is complicated at different operating conditions due to limitation of instruments to obtain in situ measurement data of membrane physical properties. This is essential since their effects are reversible. In addition, tedious experimental work is required to collect gas transport data at varying operating conditions. Recently, we have proposed a validated Soft Confining Methodology for Ultrathin Films that can be used to simulate ultrathin polysulfone (PSF) membranes upon confinement limited to 308.15 K and 2 bars. In industry application, these ultrathin membranes are operated within 298.15–328.15 K and up to 50 bars. Therefore, our proposed methodology using computational chemistry has been adapted to circumvent limitation in experimental study by simulating ultrathin PSF membranes upon confinement at different operating temperatures (298.15 to 328.15 K) and pressures (2 to 50 bar). The effect of operating parameters towards non-bonded and potential energy, free volume, specific volume and gas transport data (e.g. solubility and diffusivity) for oxygen and nitrogen of the ultrathin films has been simulated and collected using molecular simulation. Our previous empirical equations that have been confined to thickness dependent gas transport properties have been modified to accommodate the effect of operating parameters. The empirical equations are able to provide a good quantitative characterization with R2 ≥ 0.99 consistently, and are able to be interpolated to predict gas transport properties within the range of operating conditions. The modified empirical model can be utilized in process optimization studies to determine optimal membrane design for typical membrane specifications and operating parameters used in industrial applications.